2022
DOI: 10.1177/00302228221123159
|View full text |Cite
|
Sign up to set email alerts
|

“Sleep Quality and Depression Level in Nurses in COVID-19 Pandemic”

Abstract: The COVID-19 spread rapidly all over the world and pandemic process has negatively affected nurses. Sleep disorders and depression are among these negative effects. Managers' awareness of problems experienced by nurses and taking precautions will increase employee and patient satisfaction and provide quality patient care. The study was conducted in descriptive, cross-sectional and correlational design to explain nurses' sleep quality and depression levels and relationship between them during the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A meta-analysis study also showed that sleep disturbances were more frequent during the COVID-19 pandemic [ 24 ]. Other studies also reported similar results [ 25 28 ]. A systematic meta-analysis review of 250 studies on about half a million participants indicated that the estimated prevalence of sleep disorders (including poor sleep quality and insomnia), independent of any other variable, was 40% across all ages during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 79%
“…A meta-analysis study also showed that sleep disturbances were more frequent during the COVID-19 pandemic [ 24 ]. Other studies also reported similar results [ 25 28 ]. A systematic meta-analysis review of 250 studies on about half a million participants indicated that the estimated prevalence of sleep disorders (including poor sleep quality and insomnia), independent of any other variable, was 40% across all ages during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 79%
“…Poor sleep quality can contribute to depression and lower motivation to obtain pleasure in older adults with T2DM, which can negatively impact psychological status. 54 In addition, it has been found that older adults with T2DM who have poor sleep quality have less psychological resilience to relieve the symptoms of their disease and improve their condition. 55 Long-term self-management and accumulated psychological stress can increase physical and mental exhaustion, which exacerbates T2DM-associated pain and makes older adults more prone to depression.…”
Section: Discussionmentioning
confidence: 99%
“…It uses 21 questions and sums the scores to understand an individual's recent state of the three emotions. Depression was rated as mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), or very severe (≥28). Anxiety was rated as mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), or very severe (≥20).…”
Section: Dass-21mentioning
confidence: 99%
“…Depression was rated as mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), or very severe (≥28). Anxiety was rated as mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), or very severe (≥20). Stress was rated as mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), or very severe (≥34).…”
Section: Dass-21mentioning
confidence: 99%
See 1 more Smart Citation